If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2b + 10) = 12(b + -1) Reorder the terms: 2(10 + 2b) = 12(b + -1) (10 * 2 + 2b * 2) = 12(b + -1) (20 + 4b) = 12(b + -1) Reorder the terms: 20 + 4b = 12(-1 + b) 20 + 4b = (-1 * 12 + b * 12) 20 + 4b = (-12 + 12b) Solving 20 + 4b = -12 + 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. 20 + 4b + -12b = -12 + 12b + -12b Combine like terms: 4b + -12b = -8b 20 + -8b = -12 + 12b + -12b Combine like terms: 12b + -12b = 0 20 + -8b = -12 + 0 20 + -8b = -12 Add '-20' to each side of the equation. 20 + -20 + -8b = -12 + -20 Combine like terms: 20 + -20 = 0 0 + -8b = -12 + -20 -8b = -12 + -20 Combine like terms: -12 + -20 = -32 -8b = -32 Divide each side by '-8'. b = 4 Simplifying b = 4
| 15x+8=20+3x | | 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 | | 1059/10=18/1(14/13x) | | -1=-7x | | 6.2h-0.4=2.7 | | 3a+18=3(2a+3) | | X^2+12x-43=4x+5 | | -2=-7x | | -4x+6x^2+5x= | | -7.38=2.05-7.38 | | 4y+8=-2y+1 | | 24Y=72 | | 2.7+10m=7.23 | | 3a-3a^2= | | 2(x+4)+x=11 | | 16x+10=15x+2 | | 3=-4x-6 |